A whale of a legal tale : how "fishy" business behavior might be obstruction of justice - Bumgardner, Larry; Palmer, Lynda (London : Pepperdine University, Graziadio School of Business and Management, 2020)
Obstruction of justice is a timely and important topic. But exactly what conduct qualifies as the crime of obstructing justice? The question is more complicated than it might seem, as there are a plethora of federal offenses that can fall under the broad category of obstruction of justice.It is important for businesspeople to realize that obstruction of justice can include behavior that many might not consider such a serious offense, as a commercial fisherman in Florida found out the hard way.That fisherman got caught in the legal net of the Sarbanes-Oxley Act of 2002, the federal law passed by Congress after the collapse of Enron Corp. One of its sections included a new, tougher crime of obstruction of justice, and federal prosecutors used that statute to convict a fisherman for destroying evidence, which happened to be undersized red grouper.It took the U.S. Supreme Court to decide if disposing of undersized fish was prohibited by the Sarbanes-Oxley obstruction provision, and the issue came close to splitting the nine justices right down the middle. By a one-vote margin, the court ultimately concluded that the Sarbanes-Oxley obstruction crime should not apply to a commercial fisherman who improperly disposed of undersized fish.This court battle is more than an amusing fish tale. The underlying legal question has implications for the crime of obstruction of justice, as well as for how companies need to deal with business records and other potential evidence. Moreover, the case demonstrates how a law prompted by only a few corporate bad actors may end up ensnaring many unwitting businesses and victims. Finally, it should remind all businesspeople of the inherent dangers of treading even close to the line of improper or unethical behavior.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; United States; Commercial crimes -- United States -- Cases studies; Business enterprises -- Corrupt practices -- Case studies